Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.3390/ijerph14121482
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Source Generation Mechanisms for Low Frequency Noise Induced by Flood Discharge and Energy Dissipation from a High Dam with a Ski-Jump Type Spillway

Abstract: As excess water is discharged from a high dam, low frequency noise (air pulsation lower than 10 Hz, LFN) is generated and propagated in the surrounding areas, causing environmental hazards such as the vibration of windows and doors and the discomfort of local residents. To study the generation mechanisms and key influencing factors of LFN induced by flood discharge and energy dissipation from a high dam with a ski-jump type spillway, detailed prototype observations and analyses of LFN are carried out. The disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…e path and location of the high-speed water flow significantly influence the environment. Regarding the size of the flip bucket, it can be concluded that the water flow direction can be changed by changing the model size of the flip bucket or by splitting one flow into two so as to prevent landslides due to a scouring effect, thereby protecting the environment and the ecosystem from damage [19,[39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…e path and location of the high-speed water flow significantly influence the environment. Regarding the size of the flip bucket, it can be concluded that the water flow direction can be changed by changing the model size of the flip bucket or by splitting one flow into two so as to prevent landslides due to a scouring effect, thereby protecting the environment and the ecosystem from damage [19,[39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…e standard k − ε model is the simplest complete twoequation turbulence model, which has wide applicability, is economical, and achieves reasonable accuracy. It is extensively applied in the industrial flow field and in heat-exchange simulations [18,19].…”
Section: Numerical Simulation In Contrast With the Experimental Resulmentioning
confidence: 99%
See 1 more Smart Citation
“…The rough results obtained in Step 1 are interpolated linearly for each section along the flow direction. Then, Equations (11)(12)(13)(14) are added to obtain the accurate air velocity and air pressure along the flow direction with further iteration.…”
Section: Solution To the Equationsmentioning
confidence: 99%
“…If these wells are not designed sufficiently large and cannot meet the air demands, extreme negative air pressures will occur. Negative pressure can increase the possibility of cavitation and cause many secondary disasters, such as structure vibration [9,10] and low frequency noise [11,12]. It is clear that the prediction of the air demand of a spillway tunnel is fundamental work for the reliability of project design.…”
Section: Introductionmentioning
confidence: 99%